Ways of water: Run-off, irrigation and drainage - Dupriez, Hugues; Leener, Philippe de; Carter, R. (Technical Centre for Agricultural and Rural Cooperation, 1992)
Presented in manageable units with a wealth of illustrations, this book helps us understand the water around us – rain, evaporation, the infiltration of water underground, the intimate relationship between plants and water, and many other natural phenomena. It also aims to be a practical manual of solutions and techniques accessible to all – small farmers and growers, farm managers, extension staff and technicians, students and teachers.